Occurrence of fungi in water used at a haemodialysis centre - Pires-Goncalves, R. H. [UNESP]; Sartori, F. G.; Montanari, L. B.; Zaia, J. E.; Melhem, M. S. C.; Mendes-Giannini, Maria José Soares [UNESP]; Martins, C. H. G. (Blackwell Publishing, 2008)
Aims: The aim of this study was to identify and determine the diversity, occurrence and distribution of fungi in water used at a haemodialysis centre.Methods and Results: Samples in the hydraulic circuit for the distribution of the water, dialysate samples and samples of sterilization solution from dialysers were collected over a 3-month period, and 500 ml of each sample was filtered through membranes. All together 116 isolates of fungi were recovered from 89% of all water samples collected inside the haemodialysis unit, with prevalence of moulds in tap water samples and of yeasts in dialysate samples. Fusarium spp. was the most abundant genus found, whereas Candida parapsilosis was the predominant yeast species.Conclusions: This study demonstrated that various fungi were present in the water system. These data suggest the inclusion of the detection and quantification of fungi in the water of haemodialysis.Significance and Impact of the Study: The recovery of fungi from aqueous haemodialysis environments implies a potential risk for haemodialysis patients and indicates the need for continuous maintenance and monitoring. Further studies on fungi in haemodialysis water systems are required to investigate the organism ability to persist, their role in biofilm formation and their clinical significance.
Keywords: dialysis fluid monitoring; filamentous fungi; haemodialysis; microbiological quality; water